2015
DOI: 10.5455/ijmsph.2015.12122014114
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological analysis of testicular tumors: a 4-year experience

Abstract: 14 years or less, where little variation is observed. [2-7] Though the etiology of testicular cancers is not well understood, various factors such as cryptorchidism, trauma, infections, and genetic and endocrine factors appear to have a role in their development. [8] A definite geographic and racial distribution is seen in testicular tumors. The age distribution of testicular cancers is also distinct from other types of cancer. [2] Objective: The purpose of this study was to analyze the pattern and distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
6
3
0
Order By: Relevance
“…10,11 The incidence of seminoma in our study was lower than the studies of Patel MB, Reddy H and Gupta A, but similar to the study by Deore KS. 5,10,11,12 The incidence of embryonal carcinoma in our study was 15.38% which is similar to the findings by Gupta A and it is higher than Reddy H (Table 6). 11,10 Non-Hodgkin's lymphoma is an uncommon disease.…”
Section: Discussionsupporting
confidence: 90%
“…10,11 The incidence of seminoma in our study was lower than the studies of Patel MB, Reddy H and Gupta A, but similar to the study by Deore KS. 5,10,11,12 The incidence of embryonal carcinoma in our study was 15.38% which is similar to the findings by Gupta A and it is higher than Reddy H (Table 6). 11,10 Non-Hodgkin's lymphoma is an uncommon disease.…”
Section: Discussionsupporting
confidence: 90%
“…Teratoma and mixed tumors were found to occur in 7.82% of cases each. Similar observations were made by Naqvi et al [13] and Chandanwale et al [12] The incidence of seminoma in this study was comparable to the studies done by Naqvi et al [13] and Chandanwale et al [12] Deore et al [18] observed lower incidence than this study. Incidence of embryonal cell carcinoma in this study was 13.9%, a similar observation made by Chandanwale et al [12] while Naqvi et al [13] showed a higher incidence than this study.…”
Section: Discussionsupporting
confidence: 93%
“…Teratocarcinoma encountered 12.1% incidence in this study, which is comparable to the studies done by Naqvi et al [13] and Karki and Bhatta. [19] Yolk sac tumor accounted for 5.22% of this study, which was comparable to the figures 5.8% and 6.8% given by Deore et al [18] and Naqvi et al [13] Most of the cases were seen in first decade. The incidence of other mixed germ cell tumors, that is, embryonal carcinoma and seminoma and Teratoma and seminoma was 4.3% and 3.4%, respectively which is comparable to the study done by Naqvi et al [13] while higher incidence was observed by Chandanwale et al [12] The incidence of nonHodgkin's lymphoma in this study was 5.22%.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, non neoplastic lesions of testis were more common than neoplastic lesions (90.1% vs. 9.8%) which are correlating with other Indian studies as shown in Table 3. 5,[9][10][11] We found undescended testis (46.1%) as the most common non neoplastic lesion. However, none of the cases showed malignancy.…”
Section: Discussionmentioning
confidence: 99%